Strategic mapping of onion supply chains: a comprehensive analysis of production and post-harvest processes in Northwest Ethiopia - Yeshiwas, Yebirzaf; Alemayehu, Melkamu; Adgo, Enyew (Frontiers in Sustainability, 2024)
Onions constitute a significant vegetable crop in Ethiopia, serving as a crucial source of income and sustenance for smallholder farmers. However, various challenges in the production and consumption processes impede a consistent supply to the market, impacting market prices. This study focuses on a comprehensive analysis of the onion supply chain, ranging from production to post-harvest handling, to address existing production and marketing issues. The research initiative was undertaken to map the onion supply chain from farmers to consumers, intending to establish an improved marketing system in northwest Ethiopia. A critical challenge identified for onion producers in achieving maximum yield is the shortage of fertilizers. Challenges such as high costs, extended lead times, limited farmer involvement in demand estimation, and discrepancies between supplied and demanded quantities contribute to the delay in obtaining fertilizers. The study identifies six alternative channels for onion marketing, involving various actors throughout the supply chain. Key stakeholders include farmers, local collectors, brokers, transporters, wholesalers, retailers, and consumers. Packaging and sorting activities are implemented at different supply chain stages to minimize post-harvest losses. Farm-level activities, including curing, sorting, grading, and ventilating, are crucial for reducing losses. The perishable nature of onions and existing production and handling challenges exacerbate post-harvest losses. To address these issues, stakeholders and governmental organizations are urged to promote onion value-addition technologies, including the establishment of processing industries. Such initiatives can foster collaboration among all stakeholders in the onion supply chain, ensuring sustainable benefits for producers and traders.